Comprehensive whole genome analysis of Staphylococcus aureus isolates from dairy cows with subclinical mastitis - Khasapane, Ntelekwane George; Nkhebenyane, Jane; Mnisi, Zamantungwa; Kwenda, Stanford; Thekisoe, Oriel (Frontiers in Microbiology, 2024)
Staphylococcus species are the primary cause of mastitis in dairy cows across the world. Staphylococcus aureus has recently become a pathogen that is zoonotic and multidrug resistant. This study aimed to sequence whole genomes of 38 S. aureus isolates from 55 subclinical mastitis dairy cows of 7 small-scale farmers in the Free State Province, South Africa and document and their antimicrobial and virulence genes. The 38 isolates were grouped by the in silico multi-locus sequencing types (MLST) into seven sequence types (STs), that is, (ST 97, 352, 152, 243) and three new STs (ST8495, ST8500 and ST8501). Thirty-three S. aureus isolates were divided into 7 core singlenucleotide polymorphism (SNP) clusters. Amongst the 9 distinct spa-types that were detected, Spatypes t2883 accounted for the majority of isolates at 12 (31.57%), followed by t416 with 11 (28.94%) and t2844 with 5 (13.15%). The data also revealed the identification of four (4) plasmids, with Rep_N (rep20) accounting for the majority of isolates with 17 (44.73%), followed by Inc18 (repUS5) with 2 (5.26%). These isolates included 11 distinct antimicrobial resistance genes and 23 genes linked to bacterial virulence. Surprisingly, no methicillin resistance associated genes were detected in these isolates. Genome data of the current study will contribute to understanding epidemiology S. aureus genotypes and ultimately aid in developing treatment and control plans to stop the spread of mastitis in the Free State province and South Africa as a whole.